Coverage of the Euro Crisis in Spanish, German, British, and American Elite Newspapers - (:unkn) unknown (My University, 2014)
This study examined the relationships among culture, economic policy, and news content in the European economic context. The three variables can affect one another, and the effects of information and policy can influence the future of the European Union. The culture measure included opinion and government support in the news. The economic policy measure included austerity and bailout stances. Content analysis of news content from significant periods in 2011 and 2012 in elite Spanish, German, British and American news revealed differences in news coverage. The sample included 646 articles. Spanish and German news had the most coverage of the euro crisis because the events of the crisis affected Spain and Germany more than they affected Britain and the United States. The results indicated that national economic policy influenced newspaper coverage of the euro crisis to an extent. However, the culture measures did not explain the observed differences in content, showing that attitudes of journalists toward the government in a specific news culture may not always affect content.
Keywords: Britain; Economic News; Euro Crisis; European Union; Germany; Spain